Carbon-neutral light olefins production for energy decarbonization: Process development and techno-econo-environmental analysis - Zhang, Leiyu; Gao, Ruxing; Wang, Lei; Zhang, Chundong; Jun, Ki Won; Kim, Seok Ki; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng (Chemical Engineering Journal, 2023)
Low-carbon olefins, as important platform molecules, are generally produced by limited fossil energy, resulting in massive carbon emissions and intensive energy consumption inevitably. Therefore, it is necessary to develop clean and sustainable alternatives. With this in mind, three low-carbon olefin production processes using waste CO2 and green H2 were proposed, including the methanol-mediated (Option A) and Fischer-Tropsch synthesis (FTS)-based CO2-to-olefin (CTO) processes. Herein, the FTS-based CTO processes are classified into the direct (Option B) and indirect routes (Option C) without/with the reverse water–gas-shift unit. Meanwhile, rigorous process models were established, and detailed mass and energy balances of three processes were obtained with the aid of the process simulator. Moreover, in order to evaluate the feasibility and compare the differences in process performances of three proposed processes quantitatively, comprehensive techno-econo-environmental assessments of three processes were conducted at the system level. The results indicate that, firstly, from a technical perspective, the FTS-based processes are more competitive than the methanol-mediated process due to their higher energy efficiency (67.93%) and carbon utilization efficiency (84.22%). Secondly, from an economic perspective, the methanol-mediated process has a better economic prospect in the minimum olefin selling price (2527.08 $/tonne C2–C4 olefins). Lastly, from an environmental perspective, the methanol-mediated process is more environmentally friendly owing to its lower CO2-eq emissions (61.13 kg CO2-eq/tonne C2–C4). Moreover, for two FTS-based processes, the direct route is favorable in energy efficiency and minimum olefin selling price, whereas the indirect route is preferable in the carbon utilization efficiency and environmental impacts. Overall, the study provides novel approaches for the production of low-carbon olefins, and is of significant importance for reducing carbon footprint and achieving carbon neutrality.
Keywords: Carbon utilization; CO2 hydrogenation; Environmental analysis; Indirect routes; Low carbon; Low-carbon olefin; Process-models; Selling prices; Techno-Economic analysis; Utilization efficiency; CO2 hydrogenation; Environmental analysis; Low-carbon olefins; Process modelling; Techno-economic analysis